Nanoscale Delivery Systems: Actual and Potential Applications in the Natural Products Industry - Diana Simona, Antal; Florina, Ardelean; Aimee Rodica, Chis; Evelyne, Ollivier; Maria-Corina, Serban (Current Pharmaceutical Design, 2017)
Background: Compounds and extracts derived from natural sources continue to stand in the spotlight of drug design owing to their versatile interaction with enzymes, receptors and metabolic pathways. Nanomedicine offers an operative tool for the efficient delivery of natural products, in terms of increased bioavailability, targeting, and controlled release while protecting active constituents against physico-chemical alterations. The interest of the scientific community in the field of nanosized delivery of natural compounds is demonstrated by the exponential growth of the publications in this field. Aim: Beyond the presentation of successful examples of nanoscale delivery systems containing natural products, the scope of this review is to point out the yet underexplored capacities of this field with relevance for the pharmaceutical and nutraceutical market. Review: Departing from a short presentation of plant-derived natural products and strategies to obtain nanoformulations, the current work discusses nanoparticulate drug delivery systems targeting diseases of various organs and systems: skin, central nervous system, skeletal tissue, cardiovascular apparatus, and diabetes. Conclusions: While notable progress has been achieved in the preparation of nanomedicines containing selected dietary polyphenols, works dealing with crude extracts or standardized fractions are much less frequent. In fact, most of the plants with solidly documented therapeutic properties and registered in pharmacopoeias still wait to benefit from advances in the field of nanotechnology. At least for some of them, adequate nanoformulation shall contribute to their removal from the group of dietary supplements and pharmaceutical preparations with suboptimal bioavailability and efficacy.
Keywords: Natural products